Architecture Tradition and Modernity of The Building Gedhe Mataram Mosque Kotagedhe Yogyakarta - Baharrudin Purbahanggita; Eddy Prianto (Jurnal Desain, 2021)
Indonesia has various kinds of cultural wealth. The richness of this culture is most easily seen in the architectural works that have characteristics. One example of traditional Indonesian architectural work is Javanese architecture, especially the legacy of the Islamic Mataram Kingdom. Architectural works that can still be seen and used today are mosque worship buildings. Research at the Mataram Gedhe Mosque has not been found much so that it is appropriate to be the object of research. This research begins with a search for qualitative data in the form of interviews with participants. Existing data collection is done by taking pictures at several points of the mosque as well as on the details of the existing ornaments at the Mataram Gedhe Mosque. Mataram Gedhe Mosque as a place of worship is still bound by the architectural tradition of Javanese mosques. However, the Mataram Gedhe Mosque still has its novelty. Newness in architecture is an indicator of architectural modernity. The value of architectural novelty at the Mataram Gedhe Mosque is hoped to be a lesson in architectural design.